Akupresur Titik BL 32 Terhadap Nyeri Persalinan Kala I : Evidance Based Case Report (EBCR) - Khayuni, Tri Riski Nur (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Effective and painless labor pain management is an important strategy to encourage vaginal delivery and reduce the frequency of cesarean sections. One of the non-pharmacological methods that can be used to reduce labor pain is acupressure, with the BL32 point as one example. Objective: This Evidence Based Case Report (EBCR) aims to determine the effect of acupressure at the BL 32 point on first-stage labor pain. Method: This Evidence Based Case Report (EBCR) uses an evidence search method through PUBMED and Google Scholar based data which collects and analyzes previous research on the application of acupressure at the BL32 point during the first stage of labor with publication years 2014-2023. Results: There were 2 relevant articles according to the inclusion criteria. The author has applied acupressure at the BL32 point to labor pain in mowen giving birth in the first stage at the Garuda Health Center and it was found that the woman’s pain scale before the intervention was 8 while the pain scale after the intervention was 6. Literature studies, systematic reviews and meta-analyses also support that acupressure at the BL32 point can reduce the severity of labor pain in the first stage. Conclusion: The implementation of acupressure at the BL32 point has been proven to reduce pain during the first stage of labor.